What factors affect clinical decision-making about access to stroke rehabilitation? A systematic review. (February 2019) - Longley, Verity; Peters, Sarah; Swarbrick, Caroline; Bowen, Audrey
Objectives: To determine the factors affecting clinical decision-making about which patients should receive stroke rehabilitation. Methods: Data sources (MEDLINE, CINAHL, AMED and PsycINFO) were searched systematically from database inception to August 2018. Full-text English-language studies of data from stroke clinicians were included. Studies of patients were excluded. The included studies were any design focussed on clinical decision-making for referral or admission into stroke rehabilitation. Summary factors were compiled from each included study. The quality of the included studies was assessed using the Mixed Methods Appraisal Tool. Results: After removing duplicates, 1915 papers were identified, of which 13 met the inclusion criteria. Eight included studies were qualitative and one used mixed methods. A total of 292 clinicians were included in the studies. Quality of the included studies was mixed. Patient-level and organizational factors as well as characteristics of individual clinicians contributed to decisions about rehabilitation. The most often described factors were patients' pre- and poststroke function ( n = 6 studies), presence of dementia ( n = 6), patients' social/family support ( n = 6), organizational service pressures ( n = 7) and the decision-making clinician's own knowledge ( n = 5) and emotions ( n = 5). Conclusion: The results highlight a lack of clinical guidance to aid decision-making and reveal that a subjective approach to rehabilitation decision-making influenced by patient-level and organizational factors alongside clinicians' characteristics occurs across services and countries.